Effects of Dolomite Geopolymer Filler on Mechanical Properties of Glass Fibre Reinforced Epoxy Composite - S. Shahari; M.F. Ghazali; M.M. Al Bakri Abdullah; Ch. Lih Tan; M.T.M. Faheem; V.E.B. Darmawan (Archives of Metallurgy and Materials)
The effect of the incorporation of dolomite based geopolymer on the tensile and flexural properties of glass fibre reinforced epoxy composite were investigated. Composites containing different weight percentages of fillers (2.5, 5.0 and 7.5 wt.%) were fabricated using hand lay-up and vacuum bagging techniques. The experimental results showed that the dolomite based geopolymer contributed to the detrimental effect on tensile strength of the composite with 2.5 wt.% incorporation of the filler contributed to the least detrimental effect. 2.5 wt.% incorporation of dolomite based geopolymer meanwhile improved flexural strength by 13.04%.